Trade Potential between India and Central Asia. (November 2017) - Agrawal, Pradeep; Sangita, Seema
South–South bilateral trade partnerships have been growing increasingly important, and this article analyses the current patterns of bilateral trade between India and five Central Asian countries and the potential for improving them. We apply the gravity model of trade to construct a trade potential index from an Indian perspective and assess the potential for improving India's trade with Central Asia. We find that the volume of trade between India and Central Asia in 2015 could be six to ten times greater than the actual volume. Political disturbances in the countries that fall along the direct trade route are a major barrier to trade in this region; therefore, we re-examine the potential for trade using alternate routes via Iran and China. We find that the potential for greater bilateral trade between India and Central Asia continues to be positive. JEL Classification: F10, F14